Implementasi Administrasi Keuangan dalam Pengalokasian Dana Pendidikan di Sekolah Menengah Kejuruan (SMK) Bakti Karya Parigi - Risa Umami; Ilham Fauzi (J-STAF : Siddiq, Tabligh, Amanah, Fathonah, 2023)
his study aims to determine the transparency of the implementation of financial administration in the allocation of education funds. The research method used is a case study qualitative research method. Which is a type of qualitative research, where researchers conduct in-depth exploration of programs, events, processes, activities, against one or more people. The data source used is the Administrative (TU) division of the financial administration of SMK Bakti Karya Parigi with the aspect of financial administration transparency which is the guideline for SMK Bakti Karya to meet and facilitate all groups in controlling the policies implemented at SMK Bakti Karya Parigi. Financial reporting is carried out once every 3 months (quarters) in accordance with government regulations regulated in the Ministry of National Education No. 37 of 2011 concerning quarterly financial reporting. This financial administration description discusses the past 5 months in financing income and the allocation and purpose of financing